Exercise Preferences Are Different after Stroke - Geraldine Banks; Julie Bernhardt; Leonid Churilov; Toby B. Cumming (Stroke Research and Treatment)
Objective. To explore exercise preferences in stroke survivors and controls. Methods. A novel scale—the Exercise Preference Questionnaire—was developed for this study. This questionnaire, together with established assessments of physical activities, mood, and quality of life, was completed in a single assessment session. Results. Twenty-three adult stroke survivors (mean age 63, 65% male) and 41 healthy controls (mean age 61, 66% male) participated. The groups differed on 4 of the 5 a priori exercise preference factors: relative to controls, stroke survivors preferred exercise to be more structured, in a group, at a gym or fitness centre, and for exercises to be demonstrated. Factor analysis yielded 6 data-driven factors, and these factors also differentiated stroke and control groups. There was evidence that group differences were diminished when activity levels and psychological wellbeing were accounted for. Individual variability in exercise preferences and reported barriers to exercise are outlined. Conclusion. Stroke survivors have different exercise preferences, and a better understanding of these preferences can be used to inform rehabilitation programs and increase adherence.